ANTIBACTERIAL ACTIVITY OF JAVANESE CARDAMOMUM FRUIT ESSENTIAL OIL (Wurfbainia compacta) ON Propionibacterium acnes - Nofriyaldi, Ali; Rahmawati, Ayu; Endah, Sri Rezeki Nur (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
Cardamom fruit contains the essential oils cineol, terpineol and borneol which have the potential to act as antibacterials against the growth of Propionibacterium acnes. This study aimed to determine the percentage yield of essential oil and the value of the inhibition zone for the antibacterial activity of cardamom fruit oil. The research method begins with the preparation of dried simplicia from cardamom fruit, which is then distilled using water steam. The essential oil obtained was subjected to antibacterial activity using the well diffusion method. The results of the research showed that the yield of cardamom fruit essential oil was 1,66%. Cardamom fruit simple powder contains secondary metabolite compounds alkaloids, flavonoids, saponins, steroids, triterpenoids and polyphenols. The antibacterial activity test against Propionibacterium acnes at concentrations of 3%, 6%, and 12% produced inhibition zones of 3.2 mm, 4.7 mm, and 10.1 mm, respectively. Therefore, it can be concluded that at concentrations of 3% and 6%, it is included in the medium category, while at a concentration of 12%, it is included in the strong category. Keywords: Antibacterial, Oil of Cardamomum Fruit, Propionibacterium acnes, Wurfbainia compacta